Analysis of Risk Factors for Myopia in Adolescents in Urban Environments - Mohammad Husein (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Myopia or nearsightedness is a visual impairment whose prevalence is increasing, especially among adolescents living in urban areas. This study aims to analyze the risk factors that contribute to the increasing incidence of myopia in adolescents in urban areas. The risk factors studied include near visual activity, exposure to natural light, duration of digital device use, reading habits, and genetic and environmental factors. This study design used a cross-sectional approach involving 300 adolescents aged 12-18 years who were randomly selected from several schools in city X. Data were collected through questionnaires that measured visual habits, daily activity patterns, and family health history, and were strengthened by eye refraction examinations by medical personnel. Data analysis was carried out using logistic regression to identify the relationship between risk factors and the incidence of myopia. The results showed that excessive near visual activity, use of digital devices for more than 4 hours per day, and lack of exposure to natural light were significant risk factors for myopia in adolescents. In addition, genetic factors also play an important role in the predisposition of myopia. These findings are expected to provide a deeper understanding of the factors causing myopia among adolescents and become the basis for formulating effective prevention strategies.